2021
DOI: 10.1111/bph.15649
|View full text |Cite
|
Sign up to set email alerts
|

Presence of ethanol‐sensitive and ethanol‐insensitive glycine receptors in the ventral tegmental area and prefrontal cortex in mice

Abstract: Availability data statementThe data that support the findings of this study are available from the corresponding author upon reasonable request. Some data may not be made available because of privacy or ethical restrictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 77 publications
(183 reference statements)
0
1
0
Order By: Relevance
“…Consistent with this, non-synaptic taurine or glycine release onto GlyRs was found to be vital for neocortical and spinal cord development (Flint et al, 1998;Scain et al, 2010). Studies using Glra2 knockout mice have since revealed pivotal roles for GlyR α2 in retinal photoreceptor development (Young and Cepko, 2004) and the control of receptive field surrounds in retinal ganglion cells (Nobles et al, 2012;Zhang et al, 2015a), as well as modulation of ethanol intake, aversion and preference (Blednov et al, 2015;San Martin et al, 2020;Araya et al, 2021). However, a major role for GlyR α2 has been identified in dorsal cortical progenitor homeostasis and cortical interneuron migration (Avila et al, 2013(Avila et al, , 2014.…”
Section: Introductionmentioning
confidence: 68%
“…Consistent with this, non-synaptic taurine or glycine release onto GlyRs was found to be vital for neocortical and spinal cord development (Flint et al, 1998;Scain et al, 2010). Studies using Glra2 knockout mice have since revealed pivotal roles for GlyR α2 in retinal photoreceptor development (Young and Cepko, 2004) and the control of receptive field surrounds in retinal ganglion cells (Nobles et al, 2012;Zhang et al, 2015a), as well as modulation of ethanol intake, aversion and preference (Blednov et al, 2015;San Martin et al, 2020;Araya et al, 2021). However, a major role for GlyR α2 has been identified in dorsal cortical progenitor homeostasis and cortical interneuron migration (Avila et al, 2013(Avila et al, , 2014.…”
Section: Introductionmentioning
confidence: 68%
“…However, it is worth noting that the effects on membrane lipids are relatively small at clinically relevant concentrations ( Peoples et al, 1996 ). Nevertheless, ethanol at such concentrations can modulate the functions of ligand-gated ion channels, including nicotinic acetylcholine (nACh) ( Coverton and Connolly, 1997 ), GABA A ( Wick et al, 1998 ), glycine ( Araya et al, 2021 ), N-methyl-D-aspartate (NMDA) ( Peoples and Weight, 1995 ), 5-hydroxytryptamine 3 (5-HT3) ( Lovinger and White, 1991 ), ATP receptor channels ( Li et al, 1994 ), as well as voltage-gated Ca 2+ and K + channels ( Treistman et al, 1991 ). The modulation of these responses by ethanol is contingent upon activating the channels by agonists or membrane depolarization ( Treistman et al, 1991 ; Li et al, 1994 ).…”
Section: Protein Modulation Of Girk Channelsmentioning
confidence: 99%